2014
DOI: 10.1016/j.gloenvcha.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Can Protection Motivation Theory predict pro-environmental behavior? Explaining the adoption of electric vehicles in the Netherlands

Abstract: Achieving a more sustainable, environmentally friendly future has long become an embraced goal of many societies worldwide where pro-environmental behavior is found at its core. Indeed, it is widely believed that changes in behavior are needed to promote a more sustainable future. However, engaging in and sustaining such behavior often comes at a price as it often costs more (e.g., organic products are more expensive than conventional products), requires more effort (like waste separation) or even new skills (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
215
4
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(243 citation statements)
references
References 37 publications
21
215
4
3
Order By: Relevance
“…Thus, people may decide to perform SWMBs if they think that it is possible to perform them. This finding is in line with the results of prior studies [37,50,51]. Tabernero and Hernandez [52], for instance, found that people with high perceived self-efficacy reported high engagement in recycling behaviors.…”
Section: Discussion and Implications For The Development Of Communicsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, people may decide to perform SWMBs if they think that it is possible to perform them. This finding is in line with the results of prior studies [37,50,51]. Tabernero and Hernandez [52], for instance, found that people with high perceived self-efficacy reported high engagement in recycling behaviors.…”
Section: Discussion and Implications For The Development Of Communicsupporting
confidence: 91%
“…This finding is related to results from previous studies indicating a relationship between individual perceived environmental risks and pro-environmental behavior [50,55,56], such as hybrid vehicle ownership [56], electric vehicle adoption [50], and pro-environmental in a drought (e.g., biodiversity conservation and water resource protection) [40]. In the present study, reuse and recycle behaviors are simple, well-known measures that could be practiced in general.…”
Section: Discussion and Implications For The Development Of Communicsupporting
confidence: 85%
“…The results of Tan et al's [34] survey of customer preferences and acceptance of electric vehicles indicated that purchasing behaviours are affected by four factors: charge inconvenience, short battery range, cost, and psychological factors. Bockarjova and Steg [35] claimed the most important barriers for electric vehicle adoption were perceived high monetary and non-monetary costs of electric vehicles and benefits associated with the use of a conventional vehicle. Liu and Santos [36] had similar findings in China that when deciding whether to buy a hybrid electric vehicle, a consumer will consider the cost of the vehicle and the cost of operations such as battery capacity and possible speeds.…”
Section: Factors Influencing Alternative Fuel Vehicles Purchasing Behmentioning
confidence: 99%
“…Peters and Dutschke [56] found that having environmental advantages is a motivator for adopting electric vehicles. Bockarjova and Steg [35] stated that people are more likely to adopt an electric vehicle when they expect electric vehicles to decrease environmental risks. Environmental concern is a psychological factor that should affect user's attitudes towards the acceptance of full electric vehicles.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Several prior studies have found positive associations between ease of use and usefulness, ease of use and attitude, usefulness and attitude, usefulness and intention to use, and attitude and intention to use [21,36]. Related to the domain of transportation and innovative products, several prior studies have been conducted on the validity and significance of the TPB and TAM [37][38][39]. Moreover, although users can have positive attitudes toward EVs, there can be hindrances and real-world constraints in purchasing and using them.…”
Section: Modeling Social Acceptance Of Electric Vehiclesmentioning
confidence: 99%